Do Demographic Factors Affect Digitial Financial Literacy? - Fida Muthia; Agil Novriansa; Sri Andaiyani (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
The purpose of this study is to determine the socio-economic influence on digital financial literacy. This research also focuses on differences in digital financial literacy by age category. The samples in this study are generation Z, millennials, generation X and baby boomers in Indonesia. The sample is selected using criteria and around 420 participants are selected as the sample of this study. The data is collected using a survey method with a questionnaire. Data analysis in this study was carried out using regression analysis to see the causal relationship between variables. Meanwhile, the one-way ANOVA test was used to see differences in digital financial literacy by age category. The results showed that age and education have a significant effect on digital financial literacy. Meanwhile, gender and income are not the factors that influence digital financial literacy. The findings also suggest that digital financial literacy differs based in the age group. This research suggests policy makers to consider digital financial literacy as part of the knowledge offered at schools or universities and use a a different program to promote digital financial literacy in each age group.